Adobe Photoshop Express Application Enhances the Diagnosis of X-Ray Thorax of Covid-19 Patient - Ahmad Mochtar Jamil; Muslim Andala Putra; Muhammad Anas (Indonesian Journal of Medical Sciences and Public Health, 2021)
Covid-19 is a new infectious viral illness. The first one appeared in Wuhan, and within two months, it became a pandemic. Medical diagnosis is confirmed by fever, cough, shortness of breath, combined with neutrophil ratio lymphocyte analysis and chest x-ray or chest C.T. radiology imaging, with a ground-glass appearance. C.T. scans are not widely available in hospitals in Indonesia. Many hospitals only own x-ray for covid-19 as radiologic diagnostic imaging. With digital imaging capabilities, Due to the similarity of applications such as the radiological workstation, Adobe Photoshop Express will improve the capacity to diagnose Covid-19 from a chest x-ray. Adobe Photoshop Express has outstanding digital processing capabilities to enhance the presentation of images so that the efficiency of diagnosing plain x-ray thorax image cases with Covid-19 becomes easier and more manageable.